Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

how to solve
3/5e-6=-2/5(e-10)-7


Sagot :

[tex] \frac{3}{5} e-6=- \frac{2}{5}(e-10)-7 [/tex]
[tex] \frac{3}{5} e-6=- \frac{2}{5} e- \frac{2}{5}*(-10) -7 \\ \frac{3}{5} e-6=- \frac{2}{5} e+ \frac{20}{5} -7= \frac{3}{5} e-6=- \frac{2}{5} e+4 -7= \\ [/tex]
[tex] \frac{3}{5}e-6=- \frac{2}{5} e-3[/tex]      /*5
3e-18=-2e-15        /+15
3e-3=-2e            /+2e
5e-3=0              /+3
5e=3
e=[tex] \frac{3}{5} [/tex]